2018
DOI: 10.1371/journal.pone.0193471
|View full text |Cite
|
Sign up to set email alerts
|

The existence of parenting styles in the owner-dog relationship

Abstract: Parents interact with children following specific styles, known to influence child development. These styles represent variations in the dimensions of demandingness and responsiveness, resulting in authoritarian, authoritative, permissive or uninvolved parenting. Given the similarities in the parent to child and owner to dog relationships, we determined the extent to which parenting styles exist in the owner to dog relationship using the existing Parenting Styles and Dimensions Questionnaire for the parent-chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 37 publications
1
42
1
2
Order By: Relevance
“…While the effectiveness of caregiver training was repeatedly shown in educational, psychological, and behavior-analytic research, including meta-analyses (e.g., Bearss, Burrell, Stewart & Scahill 2015;Crone & Mehta, 2016;Fukkink & Lont, 2007;Ilg et al, 2018), the topic did not yet attract wide attention within the animal behavior research community (Coe et al, 2014;Howard & DiGennaro-Reed, 2014). This is surprising as similarities between owner-dog and parent-child relationships (Hare & Tomasello, 2005;Prato-Previde et al, 2003;Prato-Previde & Valsecchi, 2014;Tomasello & Kaminski, 2009;Topal, Miklósi, Csányi & Dóka, 1998;van Herwijnen et al, 2018) are well-established, and many sources rely on dog owners to follow the animal behaviorists' instructions to implement the interventions accordingly (e.g., Butler et al, 2011;Echterling-Savage et al, 2014). In this vein, previous studies suggested that training caregivers to implement interventions with integrity may benefit treatment outcomes (e.g., Belfiore et al, 2008;Fryling et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While the effectiveness of caregiver training was repeatedly shown in educational, psychological, and behavior-analytic research, including meta-analyses (e.g., Bearss, Burrell, Stewart & Scahill 2015;Crone & Mehta, 2016;Fukkink & Lont, 2007;Ilg et al, 2018), the topic did not yet attract wide attention within the animal behavior research community (Coe et al, 2014;Howard & DiGennaro-Reed, 2014). This is surprising as similarities between owner-dog and parent-child relationships (Hare & Tomasello, 2005;Prato-Previde et al, 2003;Prato-Previde & Valsecchi, 2014;Tomasello & Kaminski, 2009;Topal, Miklósi, Csányi & Dóka, 1998;van Herwijnen et al, 2018) are well-established, and many sources rely on dog owners to follow the animal behaviorists' instructions to implement the interventions accordingly (e.g., Butler et al, 2011;Echterling-Savage et al, 2014). In this vein, previous studies suggested that training caregivers to implement interventions with integrity may benefit treatment outcomes (e.g., Belfiore et al, 2008;Fryling et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The actual situation will be less positive as we assume our study sample of volunteers recruited by mainly (social) media to be skewed towards people with positive opinions about having a dog and thus willing to make the effort of filling out a research questionnaire on dogs. Unintentionally, much research on dog ownership is done with highly engaged dog owners [ 21 , 24 ], because participating in research requires effort, which average or less engaged dog owners are less likely to invest. Presently, science has not found an easy solution to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Parenting styles were measured with 32 parenting style items on a five-point Likert scale, rating the likelihood of scenarios occurring as never (score zero), nearly never (one), neutral (defined as about half of the time, two), nearly always (three) and always (four). These items were based on the Parenting Styles and Dimensions Questionnaire (32-PSDQ) commonly used with children [26] and transformed for use with dogs [23]. Here we used the 32 items measuring on the three 'original' parenting styles of authoritative, authoritarian and permissive parenting, as to facilitate comparisons of our study outcomes with similar studies done with children.…”
Section: Surveymentioning
confidence: 99%
“…Differences in how owners see and treat their dog can be studied through the recently discovered dog-directed parenting styles [ 22 , 23 ] and in humans associations exist between parenting styles and a child’s overweight, including obesity [ 24 ]. Parenting styles encompass the overarching ‘emotional climate’ in the relationship between a care provider such as a dog owner and a care receiver such as a dog [ 23 ]. This emotional climate is characterized by variation in dimensions of responsiveness and demandingness [ 25 ].…”
Section: Introductionmentioning
confidence: 99%